The effect of board’s quality on performance: a study of Canadian firms - Adjaoud, Fodil; Zeghal, Daniel; Andaleeb, Syed Saad (© 2007 Blackwell Publishing Ltd., 2016)
This article was published in the Corporate Governance: An International Review [© Wiley Online Library] and the definite version is available at : http://doi:10.1111/j.1467-8683.2007.00592.x The Journal's website is at: http://onlinelibrary.wiley.com/doi/10.1111/j.1467-8683.2007.00592.x/abstract